The Effect of Digital Marketing, Influencer Marketing and Online Customer Review on Purchase Decision: A Case Study of Cake Shop "Lu’miere" - Ratih Anggoro Wilis; Ali Faik (Petra International Journal of Business Studies, 2022)
Lu'Miere is a brand of cake shop owned by Anang Hermansyah and Ashanty. Located in Pondok Indah Jakarta, this cake shop has succeeded in attracting many cake lovers. Moreover, this store offers an interesting variety of menus and provides a unique atmosphere. This study aims to examine the effect of Digital Marketing, Influencer Marketing, and Online Customer Reviews on purchase decisions from customers of Lu'Miere. The objects used in this study are the Lu'Miere's Customers. Analysis of the data used in this study begins with direct observation and exploration to develop a conceptual framework for the study, then distributing questionnaires to 101 respondents from the customer of Lu'Miere. The results showed that Digital Marketing, Influencer Marketing, and Online Customer Review significantly affect purchasing decisions. The R2 value of 0.585 means that the percentage of the influence of digital marketing, influencer marketing, and online customer review on purchasing decisions is 58.5%. At the same time, the rest is influenced by other variables that are not included in this model.